Comparative Literature and Interdisciplinary Studies: An Analytical-Inductive Study/ الأدب المقارن والدراسات متعددة التخصصات: دراسة تحليلية استقرائية - Alharbi, Saleh (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study explores the potential of comparative literature as a field that can be effectively integrated into interdisciplinary studies. It examines the various disciplines that intersect with comparative literary studies and are often included in comparative analysis. It also investigates the concept of “image” in comparative literature, providing examples of how this old idea interacts with contemporary theoretical frameworks. Using an analytical-inductive approach, the study reaches several key findings: it identifies the interdisciplinary potential inherent in comparative literature because of its unique nature, its historical emergence in early 19th-century Europe, and its focus on the analysis of literary works written in different languages, comparative literature has exceptional opportunities for collaboration with other disciplines—opportunities not available in other fields. One of the most influential critical studies of East-West relations has significantly shaped studies across disciplines. It underscores the importance of image studies in comparative literature and its relationship to various academic disciplines through modern theoretical perspectives.